A case report: a rare case of severe aortic incompetence. Issue 3 (26th May 2020) - Sondh, Mandeep Singh; Tandon, Rohit; Gupta, Rajiv; Wander, Gurpreet Singh
Abstract: Background: Aneurysms of the sinus of Valsalva (SOV) are thin-walled outpouchings most commonly involving the right or non-coronary sinuses. Because they are asymptomatic, they are rarely discovered before they rupture and form an aorto-cardiac fistula. We present a rare case of unruptured aneurysm of the right coronary SOV burrowing into the interventricular septum with severe aortic incompetence and left ventricular dysfunction. To our knowledge, burrowing of the SOV aneurysm (SVA) into the interventricular septum and its large sac-like appearance has never been described using three dimensional (3D) echocardiography before. Case summary: A 37-year-old man presented to the cardiology outpatient department with complaints of dyspnoea and palpitations (New York Heart Association Class II–III) for the last 6 months. He was evaluated with transthoracic echocardiography which showed a large mobile sac-like structure with irregular borders bulging and prolapsing into the left ventricular cavity with each cardiac cycle along with severe aortic incompetence. On transoesophageal echocardiogram, the right coronary cusp showed malcoaptation with deformed aortic sinus causing severe aortic incompetence. Cardiac computed tomography showed sparing of right coronary artery at the origin. A diagnosis of SVA was made. The patient underwent aortic valve replacement along with partial resection of the aneurysm. The patient had an uneventful postoperative course. Follow-up echocardiography after 4 weeks showed well-seated aortic valve prosthesis with residual SVA. The ejection fraction decreased from 46–48% to 36–38%. Discussion: Comprehensive multimodality imaging can be used for management strategy of SVA.